The Italian involvement in Greece from the third century to 167 BC - Tunnicliffe, J; Tunnicliffe, John N. (1991)
﻿ The thesis begins with the question of who were those who appealed to Rome in 230 to provide the pretext for the First Illyrian War. This is followed by an analysis of the mechanics of trade and travel to Greece, and the conditions to be encountered there; also of the honorific inscriptions which provide much of the evidence for the presence. This evidence is then assessed for Delphi, the sanctuaries of Asklepios, Aitolia and other less cohesive presences. The conclusions are in terms of Rome's dealings with Greece up to and including the First Illyrian War, as affected by her allies' presence in Greece. There follows an excursus on the development of early Latin literature, its motivations, themes and relevance in historical context. The period of the Second Punic War is then analysed to see if and how traffic continued to frequent Greece, and how Rome's policy developed from the stance which she had taken in 230. This leads to a consideration of the causes of the Second Makedonian War, and of the differing policies of Flamininus and Scipio Africanus as revealed by their honours, dedications and letters in Greece. The subsequent Italian presence in Delphi, Thessaly, Aitolia, Thrace, the Aigæian, Boiotia and elsewhere is then assessed in its historical context. There is then a broad overview of the presence on Delos throughout the period, with the emphasis on the Syro-Aitolian War and the freeing of the port in 166.